Crisis Communication in Social Media on The Example of Communication of Wrocław Local Neighborhood Councils During the Flood Of 2024 - Paweł DEREK; Bartosz JASIŃSKI; Przemysław LIGENZA (Communications of International Proceedings, 2024)
This publication focuses on the aspect of communicating flood risk activities (in September 2024) of a large Polish city – Wrocław, historically experienced by the flood in 1997. The authors focus on information activities carried out by auxiliary local government units operating in the city, such as local neighborhood councils, through Facebook. The aim of the article is to identify and analyze anti-crisis measures in transport, especially of a pre-emptive and preventive nature, implemented in the period from September 11 to October 30, 2024 by Wrocław local neighborhood councils. Due to the near date of the event, this publication fills the existing gap in the literature. To conduct this study, on the one hand, an analysis of the literature on crisis phenomena and crisis communication was used, as well as the author's analysis of the collected messages shared by the surveyed entities on official profiles available in social media. Those posted on the Facebook platform were selected for analysis as the most popular in Poland. The analysis showed that in the period of potential flood risk, local neighborhood councils were involved in anti-crisis activities with varying intensity. Those that had direct flood experience from previous years showed greater involvement in the communication process and focused on anticipation and prevention in the latent and potential crisis phases.
Keywords: Crisis communication; Disastrous crisis management; social media; crisis.